Tooth Eruption Disorders: Literature Review and Clinical Case Reports - Wojda, Martyna; Wielgosz, Aleksandra (Quality in Sport, 2024)
Introduction and purpose: Tooth eruption disorders are complex issues that can affect both primary and permanent teeth. The process of tooth eruption is a natural stage of development, but it can sometimes be disrupted. Common eruption disorders include delayed eruption, tooth impaction, premature eruption, and abnormalities in the location and direction of eruption. In each case, consultation with a specialist is required, along with early diagnosis and subsequent planning of appropriate treatment. State of knowledge: Impacted teeth are a common occurrence in dentistry and they occur in 0.8–3.6% of the general population The most frequently impacted teeth, in decreasing order of prevalence, are third molars, maxillary canines, mandibular premolars, and maxillary central incisors. Factors contributing to tooth impaction can be general, local, or genetic. Impacted teeth and difficulties with eruption may be associated with complications such as follicular cysts and a variant of these cysts known as eruption cysts. Summary: Tooth eruption disorders require an individualized diagnostic and therapeutic approach. Depending on the issue, treatment may involve observation, orthodontic interventions, and in some cases, surgical procedures. Early diagnosis and appropriate treatment are crucial to prevent complications such as malocclusion, damage to adjacent teeth, or unsatisfactory aesthetics. Radiographs can help confirm the presence of impacted teeth or in some cases, CBCT may be used for more detailed imaging.